PSIKOEDUKASI MASYARAKAT TENTANG KESEHATAN MENTAL - Hartin Kurniawati; Ika Rahayu Satyaninrum; Munakhiroh El Hajar; Siskha Putri Sayekti (Universitas Muhammadiyah Luwuk, 2023)
Mental health is still an important basic need. Myths and misconceptions that Indonesians believe about mental health. For this reason, I t is necessary to educate the public about mental health properly. This activity was carried out in Pabuaran Village, Kemang District, Bogor Regency. Education about mental health aims to raise and increase public awareness about mental health. The implemntation of this activity is carried out by brainstorming, dicsussion, and games. The success of the implementation of this community service activity can be seen from changes in attitudes and behaviors that reflect a mentally healthy personality.